Synthesis and evaluation of alpha-Ag2WO4 as novel antifungal agent - Foggi, Camila C. [UNESP]; Fabbro, Maria T.; Santos, Luis P. S.; Santana, Yuri V. B. de; Vergani, Carlos E. [UNESP]; Machado, Ana L. [UNESP]; Cordoncillo, Eloisa; Andres, Juan; Longo, Elson [UNESP] (Elsevier B.V., 2017)
Because of the need for new antifungal materials with greater potency, microcrystals of alpha-Ag2WO4, a complex metal oxide, have been synthetized by a simple co-precipitation method, and their antifungal activity against Candida albicans has been investigated. A theoretical model based on clusters that are building blocks of alpha-Ag2WO4 has been proposed to explain the experimental results. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Antifungal activity; alpha-Ag2WO4; Theoretical calculations; Candida albicans